Deformation mechanism of iPP under uniaxial stretching over a wide temperature range: An in-situ synchrotron radiation SAXS/WAXS study. (2nd June 2017) - Chen, Xiaowei; Lv, Fei; Su, Fengmei; Ji, Youxin; Meng, Lingpu; Wan, Caixia; Lin, Yuanfei; Li, Xueyu; Li, Liangbin
Abstract: With a combination of homemade temperature jump extension apparatus and in-situ synchrotron radiation small and wide angle X-ray scattering (SR-SAXS and SR-WAXS) measurements, uniaxial stretching experiments of polypropylene films at 50 °C-150 °C are carried out to obtain the structure evolution routes. Three distinct features of the structure evolution are observed in temperature space, which can be described with three different deformation models, namely amorphization, crystalline block slip and melt recrystallization, respectively. Also, a refined morphology diagram in strain-temperature space is given to specify the morphology under two dimensional stretching parameter space. This work supplies a guidance for selecting processing conditions to obtain optimal structures after uniaxial stretching in industry. Graphical abstract: Highlights: In-situ SAXS and WAXS are used to track structure evolution of iPP under extension. A morphology diagram is proposed over a wide strain-temperature parameter space. Deformation mechanisms are revealed and defined into three regions.